Modern methods for studying atherosclerosis and coronary artery disease: flow cytometry - E. M. Stakhneva; Yu. I. Ragino (Бюллетень сибирской медицины)
The problem of atherosclerosis, which forms the pathological basis of coronary artery disease (CAD), is one of the most discussed ones in development of cardiovascular diseases. This chronic inflammatory disease involves interactions between different cells, and an atherosclerotic plaque is a complex immunological environment. Modern  quantitative methods  increase the understanding of the pathophysiological processes responsible  for progression of atherosclerotic plaques. Flow cytometry is a powerful modern method that allows for a complex and simultaneous cell analysis. This review is devoted to studies on atherosclerosis and CAD performed  using flow cytometry.